Implementasi Gadai (Rahn) Sawah Di Desa Sayur Mahincat Kecamatan Barumun Selatan Kabupaten Padang Lawas Dalam Perspektif Ekonomi Islam - Nur Hapipah Hasibuan; Junda Harahap; Nur Jannah Nasution (Journal of Islamic Economics and Finance, 2023)
Based on the results of the research conducted that: (1) Implementation of Pawn (Rahn) in the Islamic Economic Perspective is an agreement or contract in mu'amalah which is carried out by two parties in the form of accounts payable by submitting an item as collateral for the debt. (2) Implementation of Pawning (Rahn) Rice Fields in Sayur Mahincat Village, Barumun Selatan District, Padang Lawas Regency in an Islamic economic perspective, namely the pawnshop (rahin) comes to the pawnbroker (murtahin) to borrow some money in cash to fulfill his life needs by handing over his rice fields as collateral for debt. The right to use the collateral is controlled by murtahin until the debt is paid off and there is also the pawnbroker who manages the rice fields themselves which are used as collateral with the proceeds from the fields being divided in half with the pawn recipient. There is no time limit for repayment of the debt, the end of the mortgage is rahin has been able to pay off his debt to the murtahin. the implementation of pawning (rahn) in rice fields is in accordance with the perspective of Islamic economics because there is willingness, the principle of helping, and avoiding extortion of pawned goods, because pawning is a contract of mutual help for those who need financial assistance, this pawn contract is related to a loan agreement what desperate people do.